2015
DOI: 10.1039/c4cc08305a
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic strategy for switching the single ion anisotropy in tetrahedral Co(ii) complexes

Abstract: Four novel mononuclear tetrahedral cobalt(II) complexes containing exocyclic mesoionic ligands of molecular formulae [Co(II)(L1)(X)2(MeCN)] X = Cl (1) or Br (2) and [Co(II)(L2)(X)2(MeCN)], X = Cl (3) or Br (4) have been reported. It is found that simple substitution of L1 (O donor in 1 and 2) by L2 (S donor in 3 and 4) results in switching of the single ion magnetic anisotropy parameter (D) from positive to negative, with a significant change in magnitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 44 publications
4
78
1
Order By: Relevance
“…This type of complexes is ideal for showing enormous negative D value in d 7 electronic configuration . This correlation is valid only when the donor atoms are kept constant, which is O and S donor in the complexes 1 – 5 as the change in donor atom results in a drastic change in these parameters . The estimated D value increases from complexes 1 to 5 .…”
Section: Resultsmentioning
confidence: 96%
“…This type of complexes is ideal for showing enormous negative D value in d 7 electronic configuration . This correlation is valid only when the donor atoms are kept constant, which is O and S donor in the complexes 1 – 5 as the change in donor atom results in a drastic change in these parameters . The estimated D value increases from complexes 1 to 5 .…”
Section: Resultsmentioning
confidence: 96%
“…The double well model holds up in the case of monometallic cobalt(II) SMMs with negative D values [9,[11][12][13][14][15][16][17][18][19], but the observation of similar behaviour in monometallic cobalt(II) complexes with positive D values [20][21][22] suggests that the picture is more complex. Indeed, slow relaxation in positive-D compounds is a phenomenon that is not yet fully understood-although attempts have been made to explain it [23,24].…”
Section: Introductionmentioning
confidence: 90%
“…Finally, it was recently observed that a simple ligand field modification within a series of Co II tetrahedral complexes resulted in sign and magnitude changes in the axial ZFS parameter. The slow relaxation of magnetization was detected in all cases [70]. Tetrahedral complexes with a d 6 electronic configuration are also expected to exhibit magnetic anisotropy and some Fe II complexes with S = 2 have been investigated.…”
Section: Tetrahedral Geometrymentioning
confidence: 96%